Diverse phylogeny and morphology of magnetite biomineralized by magnetotactic cocci. (10th October 2020) - Liu, Peiyu; Liu, Yan; Zhao, Xiang; Roberts, Andrew P.; Zhang, Heng; Zheng, Yue; Wang, Fuxian; Wang, Lushan; Menguy, Nicolas; Pan, Yongxin; Li, Jinhua
Summary: Magnetotactic bacteria (MTB) are diverse prokaryotes that produce magnetic nanocrystals within intracellular membranes (magnetosomes). Here, we present a large‐scale analysis of diversity and magnetosome biomineralization in modern magnetotactic cocci, which are the most abundant MTB morphotypes in nature. Nineteen novel magnetotactic cocci species are identified phylogenetically and structurally at the single‐cell level. Phylogenetic analysis demonstrates that the cocci cluster into an independent branch from other Alphaproteobacteria MTB, that is, within the Etaproteobacteria class in the Proteobacteria phylum. Statistical analysis reveals species‐specific biomineralization of magnetosomal magnetite morphologies. This further confirms that magnetosome biomineralization is controlled strictly by the MTB cell and differs among species or strains. The post‐mortem remains of MTB are often preserved as magnetofossils within sediments or sedimentary rocks, yet paleobiological and geological interpretation of their fossil record remains challenging. Our results indicate that magnetofossil morphology could be a promising proxy for retrieving paleobiological information about ancient MTB.